Hybrid BCI System to Operate an Electric Wheelchair and a Robotic Arm for Navigation and Manipulation Tasks - Achic, F (2016)
This research proposes an integral system combining a hybrid BCI interface and shared control system for navigation and manipulation applications. In particular, the system consists of an electrical wheelchair with an embedded robotic arm that can assist a user to achieve essencial tasks such as picking up a cup of water. The proposed system uses a graphic interface that allows the user to select the possible control tasks through EEG signals based of steady state visual evocked potentials (SSVEP). On the other hand, the wheelchair is controlled by cervical movements related to head movement obtained by inertial sensors that assign navigation commands to the wheelchair, while ultrasonic sensors allow obstacle detection. Experimental results demonstrate the viability of the system and potential use as assistive technology for patients with motor paralysis conditions.